Client Requirements Management In Social Housing: A Case Study On The Residential Leasing Program In Brazil - Formoso, Carlos; Leite, Fernanda; Miron, Luciana (Penerbit Universiti Sains Malaysia, 2011)
As in other developing countries, social housing programs in Brazil have endured major changes in the last two decades, such as decentralisation in decision making, growing participation by private developers, and decreasing participation by the government, which has traditionally been responsible for social housing product development in Brazil. This has increased the complexity of those projects and created new roles and relationships for the organisations involved in social housing projects. In this context, there is a need for improving the product development process of those projects and, more specifcally, the manner in which client requirements are managed. The aim of this paper is to evaluate the Residential Leasing Program (PAR – Programa de Arrendamento Residencial), one of the most important programs for low-income families in Brazil, from the perspective of client requirements management. Two sets of case studies were carried out. The frst set involved an analysis of the product development process and highlighted opportunities for improving client requirements management. The second set of case studies involved a postoccupancy evaluation, which noted some contradictions in the way the PAR Program was conceived. The results suggest that the adoption of mass customisation strategies, which have been successful in other industries, would be benefcial to the social housing sector.